ASSESSMENT OF THE PRESENCE OF FURUNCULOSIS IN CULTURED Oncorhynchus mykiss - Filiz; Filiz Akköse (Slovenian Veterinary Research)
Furunculosis is a significant and pervasive disease affecting fresh and seawater fish globally. The disease is caused by a specific etiological agent, Aeromonas salmonicida, which leads to the formation of furuncles, or ulcerative muscle lesions, and other cutaneous manifestations such as red patches and skin discolouration. A total of 15 trout farms were visited, and 300 samples were taken from 60 individuals with an average live weight of 100-180 grams. Subsequently, the bacteria were identified through culture and MALDI-TOF. The severity of pathological symptoms correlates with the virulence of the disease. The agent has been detected in fish at temperatures between 15°C and 19°C.  40 % of the fish exhibited exophthalmus, 38.7% displayed sluggish swimming, 38.3% exhibited lethargic swimming, and 46.67 % exhibited loss of appetite. The prevalence of fish exhibiting pallor of the gills was 45%. Furthermore, 46.7% of the fish exhibited haemorrhages in the skin and fins. Ulcer formation on the skin was observed in 36.7% of the fish. An internal examination revealed the presence of bloody fluid accumulation in the intestines of the fish at a rate of 23.7%. Furthermore, 29% of the fish exhibited splenomegaly, while 23.3% displayed hepatomegaly and pigmentation changes. The aforementioned symptoms were observed with greater frequency on farms belonging to Group A. An examination of the antimicrobial susceptibility of A. salmonicida revealed that florfenicol (30 µg), enrofloxacin (10 µg), amikacin (10 µg) and gentamycin (10 µg) demonstrated sensitivity.